FACCCTS The Journal of the Faculty Association of California Community Colleges, 1995-1996 - California Community Colleges, Sacramento. Faculty Association; Martinez, Katherine; California Community Colleges, Sacramento. Faculty Association ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
This document contains the four issues of FACCCTS, the Journal of the Faculty Association of the California Community Colleges, published during the 1995-96 academic year. In the September 1995 issue, faculty members explore sensitive faculty issues: Is tenure's time up? When will part-time faculty finally receive the respect they deserve? Should the 175-day academic calendar be killed? In the November/December 1995 issue, faculty members, fundamentalists, state government, and Assembly member John Vasconcellos voice their vision for the community colleges' future. The February 1996 issue explores "Tidal Wave II," a term coined by the authors of a report from the California Higher Education Policy center for referring to the new students who will flood higher education in the next decade. FACCTS looks at who they are, their attitudes, the job market they are entering, and their vision of the future, in their own words. The May 1996 issue includes stories of some of the keynote speakers and recipients of the 1996 FACCC Awards at the 1996 FACCC Conference. A few statistics about faculty members at the state's community colleges are followed by a wide range of faculty issues. Each issue of the Journal also contains various features such as letters to the Editor, Legislative Report, FACCCTS Survey, and Book Review. (JA)
ERIC Note: Published four times a year.
FACCCTS, v2 n1-4 Sep 1995-May 1996.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Faculty; Community Colleges; Educational Legislation; Educational Planning; Futures (of Society); Student Characteristics; Teacher Attitudes; Tenure; Two Year Colleges; California Community Colleges; Collected Works, Serials